Obstructive Sleep Apnea Endophenotypes - Janna Rae Raphelson; Ana Lucia Fuentes; Breanna Holloway; Atul Malhotra (Sleep Science)
Obstructive sleep apnea (OSA) is a common disorder with major neurocognitive and cardiometabolic consequences. It is now recognized as a heterogeneous disease with multiple different underlying mechanisms (endotypes) as well as variable clinical expression of disease (phenotypes). The importance of this variability is emphasized since one variable in isolation typically explains only a fraction of the variance in OSA occurrence. This review provides an update of what is known regarding OSA heterogeneity. The importance of OSA endotypes is discussed in the context of how mechanism might affect disease management and/or design of subsequent randomized trials. Further research is recommended to provide further validation of OSA endophenotypes and how this information may influence clinical management in the future.